Biofilmes do complexo Sporothrix schenckii: formação e sensibilidade in vitro - Aguiar, Felipe Rodrigues Magalhães de (2016)
Sporotrichosis is a cosmopolitan subcutaneous mycosis, found mainly in tropical and subtropical areas of Latin America, caused by species of Sporothrix schenckii complex. The aim of this study was to demonstrate the capacity of Sporothrix schenckii complex to produce in vitro biofilms and to determine the profile of these biofilms against to classical antifungal drugs. Four species from Sporothrix schenckii complex were used: S. brasiliensis (n=10), S. schenckii sensu stricto (n=2), S. globosa (n=2) and S. mexicana (n=4). The formation of biofilms was performed by transferring inoculum of 2 x 105 conidia/mL for microdilution plates, which were incubated at 25 °C for 5 days. After each day of incubation, XTT and Crystal Violet assays were made to determine the metabolic activity and biomass of biofilm, respectively. For susceptibility tests, three different concentrations (planktonic MIC, 10 x MIC and 50 x MIC) of antifungals amphotericin B (AMB), caspofungin (CAS), ketoconazole (KTC), voriconazole (VRC) and fluconazole (FLC) were transferred to biofilm wells, which were incubated for 72 hours at 25 °C. The biofilms profile then antifungal drugs presence was determined by the XTT and crystal violet assays. Biofilms were produced in Thermanox™ coverslips for viewing by optical microscopy with congo-red staining, scanning electron microscopy and confocal microscopy. It was found that all species from S. schenckii complex are strong biofilm-forming, with no difference formation between them. Absorbance of biofilm after drug exposure showed that biomass and metabolic activity was significantly reduced (p<0.05), mainly in S. brasiliensis. Antifungal drugs tested showed metabolic activity and biomass reduction, especially at concentrations 50 times higher than the planktonic MICs, demonstrating the protective increase in sessile form when compared for planktonic form.